Prevalence, combinations and associations of components of MetS among adults aged 40 years and above from rural Kerala: a cross-sectional study - Palanichamy, Thiyagarajan; Elango, Vasantha (International Journal Of Community Medicine And Public Health, 2020)
Background: Metabolic syndrome (MetS) is a growing public health concern worldwide. A nation-wide diabetes screening campaign by the union health ministry found rural areas of selected district of Kerala had16% prevalence of lifestyle diseases. One of the objectives of WHO developed action plan for global implementation of strategies in prevention and control of non-communicable diseases (NCDs) advocates identifying MetS, a simple clinical tool, for predicting diabetes mellitus and cardiovascular diseases among population. The study aimed to estimate the prevalence of metabolic syndrome and its components among the adults aged 40 and above from rural Kerala and to determine the association with socio-demographic characteristics like co-variables of the study population. Methods: A cross-sectional study conducted among adult subjects aged 40 and above from rural field practice areas visiting RHTC. Socio-demographic profile, personal habits and history on NCDs recorded. Blood pressure and abdominal circumference measured. Fasting plasma glucose (FPG), triglyceride (TG), and high-density lipoprotein (HDL) levels were estimated. Modified NCEP-ATP III (SAS), 2009 criteria was used to diagnose MetS. Study variables were analysed for associations and comparison of means with appropriate statistical methods. Results: The prevalence of metabolic syndrome (MetS) was 29.3%. 57.9% elevated FPG, 37% Triglyceridemia, 24% sub-optimal HDL, 38.3% abdominal obesity, 38.3% elevated BP, 52% insulin resistance were recorded. Among MetS subjects 50% were in 50-59 years age group and MetS had statistically significant association with age (p value 0.005). Conclusions: Moderate prevalence of metabolic syndrome among rural subjects needs strengthening health education and screening services on NCDs.